Purchase Intention of Green Products Following an Environmentally Friendly Marketing Campaign: Results of a Survey of Instagram Followers of InnisfreeIndonesia - Wayan Weda Asmara Dewi; Fitria Avicenna; Maria Magdalena Meideline (Asian Journal for Public Opinion Research)
In Indonesia, concern about environmental protection is increasing. Thus, companies not only adjust their products but also create promotion strategies with environmentally friendly messages, called green marketing. This study identifies the effect of green marketing on purchase intentions. A quantitative method with an explanatory design was conducted. Data was gathered online. In this study, the population was @InnisfreeIndonesia Instagram followers. Thus, a direct message with the survey invitation was sent to randomly selected Instagram followers. Additional followers were invited daily for about a month until 100 responses were collected. The majority of respondents were Indonesian females, age 21-25. The results show that green products partially influence purchase intentions. Once consumers consider environmental friendly issues before buying a skin care product, they may identify whether the product is toxic-free, environmentally friendly, and holds a certification that identifies it as such. Thus, potential consumers tend to seek information to set expectations about the product they want to buy, prioritize them over other products, and to refer the product to others.